NAVHELM: HELMET INTEGRATED NAVIGATION SYSTEM - Abdul Halim, Arif Azamuddin (IRC, 2019)
Increased numbers of motorcycle on the road simultaneously affect the high number of crashes involving motorcyclist and mobile phone usage while riding have been identified as one of the reasons. Unlike cars, motorcycle lacks choices in getting visual navigation and traditional approach is not effective as rider's viewpoint is distracted because it involves head movement of the riders to see the navigation instruction. The objective of this paper is to describe the development of integrated navigation display to a helmet and validate the usability of the helmet in reducing distraction for motorcycle rider. This project utilized Node MCU ESP8266 as the microcontroller that will receive the navigational data from the navigation mobile application and display the data with using head-up display (HUD) concept. A mobile application is developed to process voice recognition to be translated as addresses to reduce manual data entry. An investigation is conducted towards two food delivery riders in using the helmet. The result shows the helmet helps motorcycle rider to reduce distraction and increase focus on the road while getting relevant navigation information through display and audio navigation. The total rating given by the rider are positively showing the helmet is helping them. By using this helmet, motorcyclist able to focus on the road and reduce phone usage while riding.